2020
DOI: 10.3389/feart.2020.00289
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ozone to a Gravity Wave Process in the UTLS Region Over the Tibetan Plateau

Abstract: In this paper, ERA5 reanalysis data from the European Center for Medium-Range Weather Forecasts and the Weather Research and Forecasting (WRF) mesoscale model are used to compare and simulate a topographic gravity wave event that occurred over the Tibetan Plateau between 18:00 on 3 May 2014 and 00:00 on 4 May 2014. The stratosphere-troposphere exchange (STE) process and its detailed characteristics during the gravity wave event are presented. The response of the upper troposphere and lower stratosphere (UTLS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Recent studies show that ozone can be influenced by non-dissipative effects of GWs (e.g. Chang et al, 2020;Gabriel, 2022). However, as these processes are not resolved in the here used model simulation and neither are included in the parameterization, this possible influence cannot be analysed here.…”
Section: Contextualizationmentioning
confidence: 97%
“…Recent studies show that ozone can be influenced by non-dissipative effects of GWs (e.g. Chang et al, 2020;Gabriel, 2022). However, as these processes are not resolved in the here used model simulation and neither are included in the parameterization, this possible influence cannot be analysed here.…”
Section: Contextualizationmentioning
confidence: 97%
“…Previous studies have indicated an 'ozone valley' near the UTLS over the SAH and its adjacent areas via analyzing a range of different data, such as MLS satellite (Guo et al, 2015), Ozone Monitoring Instrument (OMI), and Halogen Occultation Experiment (HALOE) data (Tang et al, 2019). The European Center for Medium-Range Weather Forecasts Interim Re-Analysis (ERA5) reanalysis data have also been used to study the UTLS ozone over the TP, due to its high temporal and spatial resolution (Chang et al, 2020b). The ERA5 monthly reanalysis data used in this study have a spatial resolution of 0.25°× 0.25°a nd vertical levels from 1,000 to 1 hPa with 37 layers in total.…”
Section: Datamentioning
confidence: 99%
“…With the development of observational methods (Mohanakumar et al, 2018;Chang et al, 2020a;Chang et al, 2020b;He et al, 2020;Mai et al, 2020), ozone concentrations can now be observed in different ways. For example, low ozone concentrations have been reported over the large scale topography of the TP using TOMS data, confirming the presence of an ozone low by zonal deviation (Zou, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive researches [19,20] have been conducted centred on the western United States. In contrast, in China, a major effort in STT research has been qualitatively researching dynamic mechanisms in the Tibetan Plateau and Northeast China where the pollution is not serious using multiple observations [14,[21][22][23][24][25] and Lagrange models such as HYSPLIT [26][27][28] and CLaMS [29,30]. Researches have revealed that the strong downdrafts of typhoon periphery will strengthen the STT and caused the positive ozone anomalous [31][32][33][34] in heavily polluted region.…”
Section: Introductionmentioning
confidence: 99%